2019
DOI: 10.1016/j.immuni.2019.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Skin Injury Promotes Food Anaphylaxis by Driving Intestinal Mast Cell Expansion

Abstract: Highlights d Mechanical skin injury promotes intestinal mast-cell expansion d Intestinal mast-cell expansion requires skin-derived IL-33 and gut-derived IL-25 d Intestinal mast-cell expansion requires ILC2 activation by IL-33 and IL-25 d ILC2-derived IL-4 and IL-13 directly cause intestinal mast-cell expansion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
148
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(153 citation statements)
references
References 50 publications
2
148
2
1
Order By: Relevance
“…6). It has been reported that the expansion of intestinal mast cells elicited by mechanical skin injury promotes oral anaphylaxis [39]. Therefore, our results suggest that the degranulation of intestinal mast cells could be weakened by oral administration of gliadin or peptic-GLI, leading to the suppression of anaphylactic responses.…”
Section: Discussionmentioning
confidence: 51%
“…6). It has been reported that the expansion of intestinal mast cells elicited by mechanical skin injury promotes oral anaphylaxis [39]. Therefore, our results suggest that the degranulation of intestinal mast cells could be weakened by oral administration of gliadin or peptic-GLI, leading to the suppression of anaphylactic responses.…”
Section: Discussionmentioning
confidence: 51%
“…The characterization of subpopulations of mast cells by single-cell RNA-seq, together with analysis of encoded proteins, will be of paramount importance to modulate the injury-or repair-inducing abilities of these immune cells.] For several decades mast cells were considered to play mainly proinflammatory roles in several allergic disorders, such as bronchial asthma [2][3][4]122], allergic rhinitis [5], urticaria [6,7], food allergy [8,9], anaphylaxis [10,11], atopic dermatitis [12], and angioedema [13]. During the last years, it became evident that mast cells represent an important cell during bacterial [26,27,29], fungal [29], viral [25,29], and helminth infections [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…At that time, the mast cells' distinguishing feature was the affinity of their cytoplasmic granules for certain basic dyes. For several decades, mast cells and their mediators were essentially considered to play mainly a proinflammatory role in allergic disorders, such as bronchial asthma [2][3][4], allergic rhinitis [5], urticaria [6,7], food allergy [8,9], anaphylaxis [10,11], atopic dermatitis [12], and angioedema [13]. With the appreciation of these cells as major potential sources of a myriad of cytokines and chemokines, it became evident in the 1990s that mast cells may express immunoregulatory functions [14,15].…”
mentioning
confidence: 99%
“…to crosslink IgE-bound FcΔRI to activate intestinal mast cells and basophils to elicit the food allergy phenotype (Figure 2). [44]. These cytokines initiate a Th2-skewed immune response.…”
Section: Hrf In Allergic and Immune Diseasesmentioning
confidence: 99%